2017
DOI: 10.1080/09540105.2017.1343805
|View full text |Cite
|
Sign up to set email alerts
|

Selenium supplementation through Se-rich dietary matrices can upregulate the anti-inflammatory responses in lipopolysaccharide-stimulated murine macrophages

Abstract: The accessibility of selenium from naturally enriched sources such as cereals crops can potentially be used as selenium supplements to support nutritional requirements. Dietary selenium supplementation, as Se-rich wheat extracts, on RAW264.7 macrophage cells enhanced the antioxidant capacity via augmentation of cellular selenoprotein glutathione peroxidase 1 (GPx-1) expression in the absence or presence of lipopolysaccharide (LPS) treatment. Cells were supplemented with Se in the form of sodium selenite (SS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…In recent years huge progress has been made in identifying the mechanisms by which selenium modifies the inflammatory response in murine cell lines as well as in animal models of knockout mice [ 28 , 29 , 30 ]. The available data strongly suggest that selenium mitigates the inflammatory response, but the conclusions do not directly explain whether reduced selenium body stores, as observed in our study in obese children, may enhance obesity-associated inflammation, which in turn could promote the development and progression of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years huge progress has been made in identifying the mechanisms by which selenium modifies the inflammatory response in murine cell lines as well as in animal models of knockout mice [ 28 , 29 , 30 ]. The available data strongly suggest that selenium mitigates the inflammatory response, but the conclusions do not directly explain whether reduced selenium body stores, as observed in our study in obese children, may enhance obesity-associated inflammation, which in turn could promote the development and progression of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that selenium supplementation modulates the inflammatory response in respiratory distress syndrome patients by restoring the antioxidant status of the lungs and suppressing the IL-1β and IL-6 levels ( 78 ). Selenium supplementation suppresses pathogen induced activation of NF-κB and its downstream pro-inflammatory cytokine release ( 79 ). The antiviral properties of selenium have found to be mediated through its antioxidant effects.…”
Section: Selenium (Se)mentioning
confidence: 99%
“…There are a number of works demonstrating the immunomodulatory abilities of MSA, including inhibition of the activity of the transcription factor NF-κB, which is an inflammatory marker and controls the expression of target genes for the immune response and apoptosis [95][96][97]. Activation of the NF-κB signaling pathway in various virus families increases viral replication and suppresses the apoptosis of a virus-infected cell.…”
Section: Role Of Methylseleninic Acid In the Immune System And In Pro...mentioning
confidence: 99%